EVALUATION OF ACCOUNTING INFORMATION SYSTEM FOR LENDING AT PT. BANK NEGARA INDONESIA (PERSERO) Tbk. - Ramadhan, Falah Kartika; Sari, Ditya Permata (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The development of a very fast era of information system implementation is something that is recommended especially in large banks, especially for those that have BUMN labeled status in Indonesia. So that with this very appropriate adaptation, every banking company in Indonesia must start adapting a good accounting information system (ASI) and also free from fraudulent actions. This research uses a qualitative research, which is this research method descriptive approach, which is this research in the form of information in the form of spoken or written words about the conditions that occur in the observed research object. With data collection methods with interviews, observations, and documentation this research is also one of the research with field visits on the object of research at PT. Bank Neagra Indonesia (PERSERO) Tbk. KCP branch of Brawijaya University Malang. The results of this study indicate that the implementation of the accounting information system at PT Bank Negara Indonesia (PERSERO) Tbk has been carried out well but there are still drawbacks.